Penerapan Metode Webqual 4.0 dan E-S Qual dalam Quality Measurement pada Website Madu Persada Pengolahan Madu dan Herbal - Hanifa, Nadiya; Sutresna, Jaka (Program Studi Teknik Informatika Universitas Pamulang, 2022)
The website is the first window for business owners or companies to introduce and provide more in-depth information about the company profile, besides that the website is also useful for marketing products or services produced by a company. Ownership of a website in a company is very important because it can be one proof of the professionalism of a company. A good and user-friendly website for users can be identified by measuring the quality of the website. In order to improve the quality of the Madu Persada website as a honey and herbal producer, researchers need to measure website quality using the Webqual 4.0 and E-S Qual methods. This type of research uses a quantitative descriptive approach by distributing questionnaires to 47 respondents who are determined using the slovin formula. The respondents involved in this study were users of the Madu Persada website. In this study, the data will be processed using a validity test, reliability test, the total index formula and the mean used to determine the value of the service quality of the Madu Persada website. The final calculation results for each variable are usability 83, 9%, information quality 79, 85 %, service interaction quality 77, 87%, fulfillment 79,85% and privacy 79, 56%. From the results of the study, it is known that the usability variable is the most influential variable in the quality of the Madu Persada website as a producer of honey and herbs.The final result of the overall analysis shows that the Madu Persada website as a producer of honey and herbs has very good service quality by displaying the mean (average) result of 80.2%.